Lithium ion battery recycling using high-intensity ultrasonication - Iain Aldous (Green Chemistry, 2021)
Decarbonisation of energy will rely heavily, at least initially, on the use of lithium ion batteries for automotive transportation. The projected volumes of batteries necessitate the development of fast and efficient recycling protocols. Current methods are based on either hydrometallurgical or pyrometallurgical methods. The development of efficient separation techniques of waste lithium ion batteries into processable waste streams is needed to reduce material loss during recycling. Here we show a rapid and simple method for removing the active material from composite electrodes using high powered ultrasound in a continuous flow process. Cavitation at the electrode interface enables rapid and selective breaking of the adhesive bond, enabling an electrode to be delaminated in a matter of seconds. This enables the amount of material that can be processed in a given time and volume to be increased by a factor of approximately 100. It also produces a material of higher purity and value that can potentially be directly recycled into new electrodes.